L’„eretico” Piero Gobetti e le tre “dimensioni” della storia del Risorgimento (Stato, Chiese e pluralismo confessionale, 2017)
SOMMARIO: 1. Premessa - 2. La dimensione “teorica” - 3. La dimensione “pratica” - 4. La dimensione “personale” - 5. Conclusione.The “heretic” Piero Gobetti and the three “dimensions” of the history of the RisorgimentoABSTRACT: Piero Gobetti’s “the heresy of the Risorgimento” allows to distinguish three “points of view” of the political and cultural experience of the “heretical” Gobetti, the “theoretical” one, the “practical” one and “personal” one. Three “profiles” that realized a systematic dimension, in the relationship of the Risorgimento with the “Liberal Revolution”, according to a research perspective that has never been fully analyzed. A reflection that highlights the “drama of the Risorgimento”, the “programmatic formulas” of “The Liberal Revolution” and Piero Gobetti's “clarity of authentic feelings” which moves on the “ground of heresy” with his “choice” of life.